Extraterrestrials and Generic Social Processes: Minimizing Resistance in Teaching the Reproduction of Inequality - Parrotta, Kylie; Rusche, Sarah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2011)
In this article, the authors describe a class activity that uses a combination of strategies to overcome obstacles students face when learning about the reproduction of inequality in everyday life. Based on Schwalbe et al.’s (2000) piece on "generic social processes," and following the idea of "making the strange familiar and the familiar strange," the authors had students pretend to be aliens to investigate how generic social processes are used in the United States to both maintain privilege and cope with oppression. The activity facilitates students’ understanding of how inequality is reproduced through interaction rather than by "social forces." The activity provides students with a hands-on way to grasp the reproduction of inequality from a social-psychological perspective. It also encourages students to see how valuable qualitative research is for helping sociologists understand how inequality is reproduced across contexts.